Agrarian Nationalism or “Imperial” Science? “El Sabio” Moisés S. Bertoni and Paraguayan Agricultural Science - Wilcox, Robert (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2020)
As a contribution to recent discourse over the practice of natural science in Latin America’s liberal years, this paper examines Swiss-born botanist Moisés S. Bertoni’s place in Paraguay’s agricultural development following the Paraguayan War (1864-70). The war forced leaders in a devastated Paraguay to promote the immigration of European scientific experts and farmers, with the expectation that their knowledge of modern agricultural science and practice would revitalize the nation’s agriculture and lift Paraguay out of its poverty. From the late nineteenth century Bertoni’s work and knowledge of Paraguay’s tropical and semi-tropical climate and botany shaped much of Paraguayan agricultural policy and practice. And while his contributions were influential in understanding the nation’s environment and agriculture, what is unclear is how much his approach was the product of deliberate introduction of European agricultural science or the result of autochthonous experience and his own trial and error.